Method for determining the content of aluminum in a vanadium-containing material

CN122730711BActive Publication Date: 2026-10-20PANXI VANADIUM & TITANIUM INSPECTION & TESTING INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611210345.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-20
Estimated Expiration
2046-08-11

AI Technical Summary

Technical Problem

[0011]本发明的目的在于克服现有含钒材料中铝含量测定方法存在因钒去除率低、铝回收率低以及副反应影响而导致测量结果准确性较差的问题,提出了一种含钒材料中铝含量的测定方法

Benefits of technology

1、本发明采用DCDMH在酸性水溶液中氧化低价钒,反应温度低于过硫酸铵煮沸氧化条件,有利于减少残余氧化剂和加热过程引起的空白波动。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122730711B_ABST
    Figure CN122730711B_ABST
Patent Text Reader

Abstract

The application discloses a method for determining the content of aluminum in vanadium-containing material and relates to the technical field of substance detection; the method comprises the following steps: dissolving the vanadium-containing material with hydrochloric acid and nitric acid, adding 1,3-dichloro-5,5-dimethylhydantoin under an acidic condition to oxidize low-valence vanadium into pentavalent vanadium, adjusting the pH, adding a precipitant in a molar ratio of n(S) to n(V) being 4.2-6.3:1 in terms of the amount of substance of sulfur atoms in diethyl dithiocarbamate, separating vanadium, and finally treating the obtained filtrate with perchloric acid and determining the content of aluminum by using a chrome azurol S spectrophotometric method. The method has mild oxidation conditions, can reduce the interference of a high-vanadium matrix, improve the aluminum recovery rate and determination stability, and is suitable for determining the content of aluminum in vanadium-nitrogen alloy and vanadium oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material detection technology, mainly to the field of aluminum content detection technology, and specifically to a method for determining the aluminum content in vanadium-containing materials. Background Technology

[0002] Vanadium-nitrogen alloys, vanadium oxide, and other vanadium-containing materials are important raw materials in the steel industry and functional materials manufacturing, widely used in high-strength structural steel, automotive steel, pipeline steel, tool steel, and high-end fields such as aerospace and new energy. Aluminum, as an impurity element requiring strict control, is crucial for accurate content determination in product quality control, process optimization, and performance assurance. Abnormal aluminum content directly affects the mechanical properties, processing performance, and service performance of materials; therefore, establishing accurate and reliable methods for aluminum content determination is a key aspect of quality control for vanadium-containing materials.

[0003] Among existing methods, the Chromium Azure S spectrophotometric method has become a commonly used method for determining trace aluminum due to its advantages such as high sensitivity, good selectivity, simple operation, low cost, and widespread instrument availability. In a weakly acidic to neutral medium, Chromium Azure S forms a stable blue-violet complex with aluminum ions, and quantitative analysis of aluminum is achieved by measuring absorbance. However, when applied to vanadium-containing materials, it faces a significant matrix interference problem: in materials with high vanadium content, pentavalent vanadium ions compete with Chromium Azure S for color development, severely interfering with aluminum determination and leading to distorted results. Therefore, quantitative separation of the vanadium matrix is ​​necessary before color development.

[0004] One of the classic methods for separating vanadium is extraction using copper-iron reagent (N-nitroso-N-phenylhydroxylamine ammonium salt), but this method has several serious drawbacks and is no longer able to meet the needs of modern analytical detection.

[0005] First, there are high occupational health risks. Copper and iron reagents are classified as Group 2B carcinogens by the International Agency for Research on Cancer and as reasonably expected human carcinogens by the U.S. National Toxicology Program; long-term exposure increases the occupational health risks for laboratory personnel.

[0006] Secondly, the separation effect and aluminum recovery rate are easily affected by the extraction conditions. Studies have shown that the acidity, reagent state, and phase separation process in the copper-iron reagent extraction operation can all seriously affect the degree of vanadium removal; residual vanadium will interfere with the color development of chromium azurite S, while the entrainment loss of aluminum will lead to lower measurement results.

[0007] Third, the reagents have poor stability. Copper and iron reagents are heat-sensitive and easily decompose at high temperatures; they are also light-sensitive, with light accelerating their deterioration, causing their color to change from white to yellow and then to brown; in solution, they are prone to redox reactions and become ineffective. These instabilities lead to fluctuations in separation results and poor reproducibility, further affecting the reliability of the measurement results.

[0008] Fourth, there is still room for improvement in the oxidation process. Existing methods often use ammonium persulfate to oxidize low-valent vanadium to pentavalent vanadium, which usually requires boiling or a high-temperature reaction. When the amount of oxidant added, the heating time, or the residual oxidant is not properly controlled, it will increase blank fluctuations and affect subsequent precipitation and color development.

[0009] Fifth, the process is cumbersome and environmentally unfriendly. The copper-iron reagent method requires the use of organic solvents for extraction, which involves many steps and is time-consuming. Furthermore, organic solvents pose safety hazards and environmental pollution problems, such as being flammable, explosive, and toxic.

[0010] It is evident that existing methods for determining aluminum in vanadium-containing materials suffer from problems such as strong oxidation conditions, volatile vanadium separation from the matrix and aluminum recovery rates, and numerous operational steps. Therefore, there is a need to establish a method that can control the vanadium valence state under milder conditions, quantitatively separate high-content vanadium, and accurately determine aluminum. Summary of the Invention

[0011] The purpose of this invention is to overcome the problems of poor accuracy of measurement results caused by low vanadium removal rate, low aluminum recovery rate and side reaction effects in existing methods for determining aluminum content in vanadium-containing materials, and to propose a method for determining aluminum content in vanadium-containing materials.

[0012] To achieve the above objectives, the present invention provides a method for determining the aluminum content in vanadium-containing materials, comprising the following steps: S1: Add hydrochloric acid and nitric acid to the vanadium-containing material, heat until completely dissolved, and cool to obtain an acidic sample solution; S2: After adding 1,3-dichloro-5,5-dimethylhydantoin (DCDMH, dichlorohydantoin) to the acidic sample solution, an oxidation reaction is carried out at 40-70℃ to obtain a mixed solution containing pentavalent vanadium. S3: Adjust the pH of the mixed solution to 3.6-5.6, add diethyldithiocarbamate solution for precipitation treatment, and obtain aluminum-containing filtrate after solid-liquid separation; S4: Add perchloric acid to the aluminum-containing filtrate, heat to carry out the decomposition reaction, cool and make up to volume to obtain the test solution; S5: The aluminum in the test solution was quantitatively detected using the Chromium Azure S spectrophotometric method, and the measurement results were obtained.

[0013] This invention discloses a method for determining the aluminum content in vanadium-containing materials. It uses DCDMH as an oxidant for low-valent vanadium and combines it with diethyldithiocarbamate as a precipitant. This method utilizes the characteristic that DCDMH can provide available chlorine through N-Cl bonds in acidic aqueous solutions, thereby oxidizing low-valent vanadium to pentavalent vanadium at lower temperatures (mild reaction conditions, stable process, self-regulating oxidation process, and few side reactions), significantly reducing the impact on vanadium ion precipitation and spectrophotometric determination results, resulting in more accurate measurements. Furthermore, it specifically limits the amount of DDTC added and the pH value during precipitation, significantly improving the removal rate of vanadium ions and the recovery rate of aluminum ions. This significantly reduces the interference of vanadium ions on the color development of Chromium Blue S and reduces aluminum entrainment loss, thus significantly improving the accuracy of aluminum ion determination. The method of this invention is simple, controllable, low-cost, widely applicable, and highly accurate, making it suitable for large-scale, high-precision determination of aluminum content in vanadium-containing materials.

[0014] In step S1, the concentration of hydrochloric acid is preferably 4.5–6.0 mol / L, and the concentration of nitric acid is preferably 0.25–1.75 mol / L.

[0015] The actual amount of hydrochloric acid and nitric acid added is based on the complete dissolution of the sample and the ability to remove excess acid subsequently; preferably, the volume ratio of hydrochloric acid to nitric acid is 10:1.

[0016] Preferably, the pH value of the resulting acidic sample solution is not greater than 1.

[0017] Preferably, the vanadium-containing material is a vanadium-nitrogen alloy and / or vanadium oxide.

[0018] Preferably, the melting temperature after heating is 60-90℃.

[0019] In step S2, the amount of DCDMH added preferably satisfies n(Cl):n(V) = 2 to 4:1, more preferably 3:1. Here, n(Cl) is the amount of chlorine atoms contained in the two N-Cl bonds of the DCDMH molecule, calculated as n(Cl) = 2m(DCDMH)P / M(DCDMH); P is the mass fraction of DCDMH, M(DCDMH) = 197.02 g / mol. n(V) is calculated based on the sample mass, the mass fraction of vanadium in the sample, and the molar mass of vanadium of 50.9415 g / mol.

[0020] The pH value of the oxidation reaction system is preferably not greater than 2 (when the pH value is greater than 2, hydrochloric acid can be added to adjust it); within this acidity range, DCDMH provides available chlorine in the aqueous phase and oxidizes trivalent and tetravalent vanadium to pentavalent vanadium; compared with the ammonium persulfate oxidation process that requires boiling, the reaction temperature of this step is lower; after DCDMH is added, it should be stirred thoroughly, and the oxidation endpoint is taken as the specified reaction time or the verified valence state determination result, and the reaction time is preferably 3 to 10 min.

[0021] In step S3, the diethyldithiocarbamate is preferably sodium diethyldithiocarbamate (DDTC) or potassium diethyldithiocarbamate (KDDTC). When calculating its amount of substance, the appropriate molar mass should be used based on the anhydrous or hydrated form and reagent purity actually used.

[0022] The concentration of the diethyldithiocarbamate solution is preferably 40–80 g / L; within this concentration range, the required solution volume should be calculated based on the actual amount of vanadium in the sample.

[0023] Preferably, before adding the precipitant, the pH of the mixed solution is pre-adjusted to 3.0–3.5 with ammonia (preferably 1+1), and then adjusted to pH 3.6–5.6, preferably pH 4.0, with an acetate-sodium acetate buffer (preferably with an acetate concentration of 0.10 mol / L and a molar ratio of acetate to sodium acetate of 1:1). The pre-adjustment is used to neutralize residual strong acid after digestion, and the buffer is used to stabilize the acidity of the precipitation reaction. The buffer cannot replace the neutralization step for large amounts of strong acid.

[0024] Preferably, in the diethyldithiocarbamate solution, the molar ratio of sulfur atoms to vanadium ions in the mixed solution is 4.2–6.3:1, more preferably 5.25:1. Below 4.2:1, the vanadium removal rate is insufficient; within the range of 4.2–6.3:1, both the vanadium removal rate and aluminum recovery rate remain at a high level; above 6.3:1, precipitate entrainment or surface adsorption will cause the aluminum recovery rate to decrease.

[0025] Preferably, solid-liquid separation is achieved using double-layer slow-speed quantitative filter paper; this results in better separation.

[0026] In step S4, the mass fraction of perchloric acid is preferably 70-72%; the amount of perchloric acid added is preferably 2-3 mL per 0.1 g of vanadium-containing material; after adding the perchloric acid, heat until white fumes are emitted under conditions equipped with a dedicated ventilation system for perchloric acid, and continue heating for 5-15 minutes to decompose residual organic matter; the material must not be evaporated to dryness during the operation. After cooling, dissolve in water and make up to a final volume.

[0027] In step S5, 2,4-dinitrophenol is preferably used as an indicator. Ammonia is used to adjust the acidity, and sulfuric acid is used to adjust it if necessary. Chromium azurite S solution, hydroxylamine hydrochloride solution, and hexamethylenetetramine buffer solution are added sequentially, and the absorbance is measured at 550 nm. The sample and the working curve should use the same colorimetric volume, reagent addition order, colorimetric time, and reference conditions, and the entire process blank should be subtracted.

[0028] The beneficial effects of this invention are: 1. This invention uses DCDMH to oxidize low-valent vanadium in an acidic aqueous solution. The reaction temperature is lower than that of ammonium persulfate boiling oxidation, which helps to reduce residual oxidant and blank fluctuations caused by the heating process.

[0029] 2. This invention combines DCDMH oxidation with diethyl dithiocarbamate precipitation and separation, and controls the precipitation pH and the precipitant / vanadium molar ratio, which can significantly improve the degree of vanadium removal and aluminum recovery rate.

[0030] 3. This invention uses aqueous precipitation filtration instead of copper and iron reagents and organic solvent extraction, which can reduce the use of high-risk reagents and organic solvents and simplify the separation operation.

[0031] 4. This invention is applicable to the determination of aluminum in high-vanadium matrices such as vanadium-nitrogen alloys and vanadium oxide, and has good accuracy, precision and matrix adaptability.

[0032] 5. The full-process blank, low-level spiked and comparative tests show that the detection limit of the method of the present invention is lower than that of the ammonium persulfate-chromium azurite S comparative method and the direct determination comparative method of ICP-OES under high vanadium matrix set in this application; the conclusions are based on the data in Tables 2 to 5 after verification by the original experimental records. Attached Figure Description

[0033] Figure 1 The X-ray diffraction patterns of vanadium-DDTC precipitates obtained with different DDTC addition amounts (T1-T5) in Example 2 of the present invention are shown.

[0034] Figure 2 The image shows scanning electron microscope images of vanadium-DDTC precipitates obtained with different amounts of DDTC added (T1-T5) in Example 2 of the present invention.

[0035] Figure 3 This is the energy dispersive spectroscopy (EDS) analysis diagram of the vanadium-DDTC precipitate in Example 2 (T1) of the present invention.

[0036] Figure 4 This is a graph showing the effect of the DDTC to vanadium molar ratio on vanadium removal rate and aluminum recovery rate in Example 2 of the present invention. Detailed Implementation

[0037] The technical solution of the present invention will be further described in detail below with reference to the embodiments.

[0038] Example 1

[0039] A method for determining the aluminum content in vanadium-containing materials, comprising the following steps: S1: Weigh 0.1000 g of vanadium-nitrogen alloy, add 20 mL of 5.0 mol / L hydrochloric acid and 2 mL of 1.0 mol / L nitric acid, place on a hot plate set at 280℃ and heat until the sample is completely dissolved. Continue heating until the solution volume is about 3 mL, avoiding evaporation to dryness. After cooling, add about 30 mL of water to dissolve the salts, obtaining an acidic sample solution with a pH value not greater than 1. S2: Calculate n(V) based on the mass fraction of vanadium in the sample, add DCDMH at a ratio of n(Cl)∶n(V)=3∶1, stir and react at 60℃ for 5 min to obtain a mixed solution containing pentavalent vanadium; S3: Slowly pre-adjust the pH of the mixed solution to 3.5 with ammonia (1+1), then adjust it to pH 4.0 with acetate-sodium acetate buffer (acetate concentration of 0.1 mol / L, molar ratio of acetate to sodium acetate 1:1); add 60 g / L DDTC solution at n(DDTC):n(V) = 5.25:1, stir and let stand to precipitate vanadium, filter with double-layer slow quantitative filter paper, wash the precipitate thoroughly and combine the filtrate and washings to obtain aluminum-containing filtrate; S4: Add 3.0 mL of 70% perchloric acid to the aluminum-containing filtrate, heat it in a dedicated perchloric acid ventilation system until white fumes are emitted and continue heating for 9 minutes, without evaporating to dryness; after cooling, add 30 mL of water, transfer to a 100 mL volumetric flask, and dilute to volume with water to obtain the solution to be tested; S5: Transfer 5.00 mL of the test solution to a 100 mL volumetric flask, add 2 drops of 2 g / L 2,4-dinitrophenol indicator, adjust with ammonia (1+1) until the yellow color just appears, then adjust with sulfuric acid solution until the yellow color just disappears; add 5.00 mL of 0.6 g / L chromaine S solution, 2.00 mL of 80 g / L hydroxylamine hydrochloride solution and 5.00 mL of 400 g / L hexamethylenetetramine solution in sequence, make up to volume with water, mix well and let stand for 10 min, measure the absorbance at 550 nm with water as a reference, and subtract the blank of the whole process.

[0040] Working curve and calculation: Transfer 0, 1.00, 2.00, 3.00, 4.00, and 5.00 mL of 5 μg / mL aluminum standard working solution, corresponding to aluminum amounts of 0, 5, 10, 15, 20, and 25 μg, respectively. Develop and measure the color under the same conditions as in step S5. Linearly fit the net absorbance A to the aluminum amount mAl (μg), obtaining A = 0.0252mAl - 0.0079, R² = 0.9994. The aluminum mass fraction is calculated as w(Al) / % = mAl × V / (Va × ms) × 10⁻¹⁰. -4 The calculation is performed, where V is the final volume of the test solution (mL), Va is the aliquot volume (mL), and ms is the sample mass (g). According to the parameters of this embodiment, a sample with an aluminum content of approximately 0.33% corresponds to approximately 16.5 μg of aluminum under aliquot conditions of 5.00 mL, falling within the 0–25 μg working curve range.

[0041] Example 2

[0042] Based on Example 1, only the molar ratio of DDTC to vanadium was changed, and the vanadium removal rate and aluminum recovery rate were measured respectively. Each condition was measured in parallel 3 times, and the results are shown in Table 1.

[0043] Table 1 Vanadium removal rate and aluminum recovery rate at different DDTC dosages

[0044] Table 1 shows that when the ratio of n(S in DDTC) to n(V) is less than 4.2:1, vanadium precipitation is incomplete, and both vanadium removal rate and aluminum recovery rate increase with increasing precipitant dosage. When the molar ratio is 4.2–6.3:1, the vanadium removal rate is 99.0%–99.5%, and the aluminum recovery rate is 99.2%–99.7%. After the molar ratio increases to 7.35:1, the vanadium removal rate does not improve further, while the aluminum recovery rate drops to 95.3%. Therefore, the preferred molar ratio range is 4.2–6.3:1. Figure 1 The main diffraction peaks are consistent with the vanadium-DDTC reference phase (T6-T7 are basically the same as T5, so they are not shown in the figure). Figure 2 The morphology of the precipitate gradually changed from agglomerated particles and spherical particles to lamellar aggregates as the amount of DDTC added (T6-T7 were basically the same as T5, so they are not shown in the figure). Figure 3 The detection of characteristic elements such as V and S (using T5 as the sample) can serve as supplementary evidence for the formation of vanadium-sulfur coordination precipitates. EDS is a semi-quantitative analysis and is not used alone to determine the precise stoichiometric composition of the precipitate. Figure 4 The preferred molar ratio window is displayed visually.

[0045] Comparative Example 1

[0046] Based on Example 1, copper-iron reagent extraction and separation were used instead of DDTC precipitation and separation, with all other conditions remaining the same; vanadium removal rate, aluminum spiked recovery rate, and aluminum determination results were recorded.

[0047] Comparative Example 2

[0048] Based on Example 1, DCDMH was replaced with 5.00 mL of 200 g / L ammonium persulfate solution, and the oxidation was completed by boiling for 5 min. The remaining steps were the same as in Example 1.

[0049] Comparative Example 3

[0050] Based on Example 1, ammonium persulfate boiling oxidation was used instead of DCDMH oxidation, and copper-iron reagent extraction separation was used instead of DDTC precipitation separation, with the other conditions remaining the same.

[0051] Comparative Example 4

[0052] Inside the fume hood, 4.58 mL of sodium hypochlorite solution, calibrated by iodometric titration and with an effective chlorine concentration of 1.000 mol / L, replaced DCDMH. This addition volume was calculated based on 0.1000 g of sample, a vanadium mass fraction of 77.73%, and n(Cl):n(V) = 3.00:1. The sodium hypochlorite solution was added slowly, with the remaining steps identical to those in Example 1. When the vanadium determination value of the sample or the measured effective chlorine concentration of sodium hypochlorite changed, the added volume was corrected according to the actual n(V) and c(effective chlorine).

[0053] Comparative Example 5

[0054] 0.50 mL of 30% hydrogen peroxide solution was used to replace DCDMH. This amount was calculated based on 0.1000 g of sample, 77.73% vanadium by mass, and n(H2O2):n(V) = 3.00:1. The oxidation reaction was carried out at 60°C for 5 min, and the remaining steps were the same as in Example 1. When the vanadium value of the sample changed, the amount added was corrected proportionally to the actual n(V).

[0055] Comparative Example 6

[0056] Without adding an oxidizing agent, the remaining steps are the same as in Example 1.

[0057] Experiment Example 1: Comparison of Accuracy and Precision

[0058] The certified reference material for vanadium-nitrogen alloys (No. YSBC28650a-2023, 837#; aluminum certified value 0.33%) was used in Examples 1 and Comparative Examples 1-6 to determine the vanadium-nitrogen alloy content. Five unspecified samples were prepared independently for each method and the determination was performed. Five spiked samples were also prepared independently for each method. After the sample dissolution in step S1 and before the addition of the oxidant, 1.00 mL of aluminum standard solution with a concentration of 50.0 μg / mL was accurately added, which is equivalent to adding 50.0 μg of aluminum to 0.1000 g of sample, i.e., increasing the aluminum mass fraction by 0.0500%. The results are shown in Table 2.

[0059] Table 2. Accuracy and precision results of Example 1 and Comparative Examples 1-6

[0060] Aluminum spiked recovery rate is calculated as R = [(w1 - w0) / w 加 The value is calculated as 100%, where w1 is the measured aluminum content of the spiked sample, w0 is the measured aluminum content of the unspiked sample using the same method, and wadd is the theoretical aluminum mass fraction added, which is 0.0500% in this experiment. The aluminum certification value of 0.33% is only used to evaluate the accuracy of the determination and is not directly substituted into the spiked recovery formula.

[0061] Table 2 shows that in Example 1, the vanadium removal rate was 99.6%, the aluminum spiked recovery rate was 99.7%, and the average aluminum content was 0.3258%, which differed from the accepted value of 0.3300% by -0.0042 percentage points, with a relative deviation of -1.27% and an RSD of 1.49%. Compared with Comparative Example 2, which only replaced DCDMH with ammonium persulfate, Example 1 maintained a high recovery rate while the measured results were closer to the accepted value, and the RSD decreased from 2.54% to 1.49%. Compared with Comparative Example 5, which replaced DCDMH with hydrogen peroxide, the vanadium removal rate increased from 95.7% to 99.6%, the aluminum spiked recovery rate increased from 95.7% to 99.7%, and the RSD decreased from 3.43% to 1.49%. In Comparative Example 6, without the addition of an oxidant, the vanadium removal rate, aluminum spiked recovery rate, and measurement precision were all significantly reduced. The above results indicate that, under the high-vanadium matrix and operating conditions specified in this experiment, the combination of DCDMH oxidation and DDTC separation can effectively remove vanadium, recover aluminum, and achieve high accuracy and precision in measurement.

[0062] Experimental Example 2: Comparison of Limit of Detection and Limit of Quantification

[0063] The detection limit tests were performed using the method of this invention (Example 1), the ammonium persulfate-chromium azurite S method of Comparative Example 2, and the ICP-OES method. High-vanadium matrix blanks were prepared using aluminum-free high-purity vanadium reagent to ensure the vanadium content was equivalent to that of the test sample. For each method, the mass fraction of aluminum in the sample was calculated based on 0.1000 g of sample and a final volume of 100 mL. Before ICP-OES determination, the digestion solution was diluted 10-fold, and a vanadium matrix-matched standard series and adjacent background correction were used. Eleven high-vanadium matrix blanks were prepared independently for each method and measured according to their respective complete procedures. The standard deviation (s) of the blank results was used as the criterion. b Calculate LOD=3s b LOQ=10s b The results are shown in Table 3.

[0064] Table 3. Comparison of the limits of detection throughout the process for different methods in high-vanadium matrices.

[0065] The detection limits in Table 3 are based on LOD=3. s b Calculations were performed with the limit of quantitation (LOQ) set at 10. s b The relative limit of detection (LOD) is calculated as the ratio of the LOD of each method to that of the method of this invention. The standard deviation of the blank for the entire process of the DCDMH-DDTC-chrome azure S method of this invention is 0.00140%, the LOD is 0.00420%, and the LOD is 0.01400%. The LOD and LOD of the ammonium persulfate-chrome azure S method are 0.01080% and 0.03600%, respectively, which is 2.57 times that of the method of this invention. The LOD and LOD of the ICP-OES direct determination method are 0.00630% and 0.02100%, respectively, which is 1.50 times that of the method of this invention. Based on the LOD, the method of this invention reduces detection by 61.1% compared to the ammonium persulfate-chrome azure S method and by 33.3% compared to the ICP-OES direct determination method. The above results indicate that, under the same sampling amount, constant volume, high vanadium matrix, and full-process blank evaluation conditions, the full-process blank fluctuation and detection limit of the method of the present invention are lower than those of the two comparative methods, which is beneficial for the determination of low aluminum content in high vanadium matrix.

[0066] Experimental Example 3: Spiking Recovery Tests of Different Vanadium-Containing Materials

[0067] Low-aluminum vanadium-nitrogen alloy, vanadium-nitrogen alloy standard material, and vanadium pentoxide were selected as representative samples. The background aluminum content of the samples was first determined according to Example 1. Then, different levels of aluminum standard solution were added, and each level was independently measured in parallel 6 times. The spiked recovery rate was calculated as (spike sample measurement value - background sample measurement value) / spiked amount × 100%, and the results are shown in Table 4.

[0068] Table 4. Aluminum Spike Recovery Results in Different Vanadium-Containing Materials

[0069] The spiked recovery rate in Table 4 is calculated as R = (measured value after spike - background value) / spiked amount × 100%. Taking the vanadium-nitrogen alloy standard material as an example, R = (0.375% - 0.326%) / 0.050% × 100% = 98.0%.

[0070] As shown in Table 4, when the method of the present invention is used for low-aluminum vanadium-nitrogen alloys, vanadium-nitrogen alloy standard materials, and vanadium pentoxide, the aluminum spike recovery rate is 98.0% to 101.0%, and the RSD is 1.3% to 2.4%, indicating that the method has good applicability to different vanadium-containing materials.

[0071] Experimental Example 4: Robustness Test of Key Reaction Conditions

[0072] Using a vanadium-nitrogen alloy standard material with an aluminum content of 0.33% as the sample, and based on the conditions of Example 1, only one factor was changed each time, while the other conditions remained unchanged. Before the determination, an aluminum standard solution equivalent to 0.050% of the aluminum mass fraction in the sample was added. Each condition was measured in parallel three times to investigate the effects of small changes in oxidation temperature, oxidation time, precipitation pH, and the molar ratio of DDTC to vanadium on the aluminum spike recovery rate. The results are shown in Table 5.

[0073] Table 5. Robustness results of the method when key conditions change slightly.

[0074] As shown in Table 5, when the oxidation temperature, oxidation time, precipitation pH, or molar ratio of S to vanadium in DDTC were slightly changed near the baseline conditions of Example 1, the aluminum spike recovery rate was 98.9% to 100.2%, and the RSD was no greater than 1.9%, indicating that the method has good condition robustness.

[0075] In Table 5, pH 4.0 is the pH when DDTC is added for vanadium precipitation separation; the DCDMH oxidation stage still maintains the acidic conditions described in Example 1, with a pH not greater than 2.

[0076] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for determining the aluminum content in vanadium-containing materials, characterized in that, Includes the following steps: S1: Add hydrochloric acid and nitric acid to the vanadium-containing material, heat until completely dissolved, and cool to obtain an acidic sample solution; S2: After adding 1,3-dichloro-5,5-dimethylhydantoin to the acidic sample solution, an oxidation reaction is carried out at 40-70℃ to obtain a mixed solution containing pentavalent vanadium. S3: Adjust the pH of the mixed solution to 3.6-5.6, add diethyldithiocarbamate solution for precipitation treatment, and obtain aluminum-containing filtrate after solid-liquid separation; in the diethyldithiocarbamate solution, the ratio of the amount of sulfur atoms to the amount of vanadium ions in the mixed solution is 4.2-6.3:

1. S4: Add perchloric acid to the aluminum-containing filtrate, heat to carry out the decomposition reaction, cool and make up to volume to obtain the test solution; S5: The aluminum content in the test solution was determined by the Chromium Azure S spectrophotometric method.

2. The determination method according to claim 1, characterized in that, In step S1, the vanadium-containing material is a vanadium-nitrogen alloy and / or vanadium oxide.

3. The determination method according to claim 1, characterized in that, In step S1, the concentration of hydrochloric acid is 4.5–6.0 mol / L, and the concentration of nitric acid is 0.25–1.75 mol / L.

4. The determination method according to claim 1, characterized in that, In step S2, the molar ratio of chlorine atoms to vanadium ions is 2 to 4:1, based on the amount of chlorine atoms contained in the N-Cl bond of 1,3-dichloro-5,5-dimethylhydantoin.

5. The determination method according to claim 1, characterized in that, In step S3, the diethyldithiocarbamate is at least one of sodium diethyldithiocarbamate and potassium diethyldithiocarbamate.

6. The determination method according to claim 1, characterized in that, In step S3, the concentration of the diethyldithiocarbamate solution is 40–80 g / L.

7. The determination method according to claim 1, characterized in that, In step S3, before adding the diethyldithiocarbamate solution, the pH of the mixed solution is pre-adjusted to 3.0-3.5 with ammonia water, and then adjusted to pH 3.6-5.6 with an acetate-sodium acetate buffer solution.

8. The determination method according to claim 1, characterized in that, In step S3, the molar ratio of diethyldithiocarbamate to vanadium is 5.25:

1.

9. The determination method according to claim 1, characterized in that, The solid-liquid separation in step S3 is performed using double-layer slow quantitative filter paper filtration.

10. The determination method according to claim 1, characterized in that, In step S4, the mass fraction of the perchloric acid is 70-72%.

Citation Information

Patent Citations

  • Method for determining pentavalent vanadium in vanadium slag, and application thereof

    CN107655882A

  • Method for detecting content of vanadium in vanadium-containing alloy

    CN112697956A